Muscle synergy during free throw shooting in basketball is different between scored and missed shots - Matsunaga, Naoto; Oshikawa, Tomoki (Frontiers in Sports and Active Living, 2022)
The current study investigated the differences in synergy during a free throw in basketball and compared synergies between scored and missed shots. A total of six men's college basketball players participated in this study. A wireless electromyographic system was used to measure the activity of 16 trunk, and upper and lower extremity muscles while completing the free throw. In total, three scored and missed shots each were analyzed to extract the synergies using non-negative matrix factorization. Overall, four synergies were extracted from the successfully made shots, and three synergies were extracted for the missed shot; two synergies were shared between scored and missed shots. The one synergy that contributes to the shoulder flexion was used to set the ball and activate the initial stage of the free throw. Another synergy that contributes the palmar flexion was used to release the ball and activate the final stage of the free throw. The other two synergies in scored shot contribute to lower and upper limb extension in sequence to promote the energy transfer in the middle to the final stage of the free throw. On the other hand, there was only a synergy that corresponded to the middle to the final stage of the free throw extracted from the missed shot. Since the movements of the lower and upper extremity extensions are performed even on a missed shot, we believe that working the from the lower to the upper limb “in sequence,” rather than working the lower and upper limbs “simultaneously,” may influence the success of the shot.